Synthesis of Imidazolidines, Saccharins and Chromone Bearing Imidazolidine Ring - Lee, Yong-Gyun; Yoon, Jin-Hwan; Kim, Jong-Sik; Song, Ju-Hyun; Kim, Yun-Young; Jung, Dai-Il; Hahn, Jung-Tai (Asian Journal of Chemistry, 2011)
As a part of a research program related to the synthetic study of pharmacologically and agrochemically interesting imidazolidines, we synthesized imidazolidines 8, 9, 10, saccharins 12, 13 and chromone 17 bearing imidazolidine-2,4,5-trione or 2-thioxoimodazolidine-4,5-dione rings.